Land Use Planning of Way Betung Watershed for Sustainable Water Resources Development of Bandar Lampung City - Yuwono, Slamet Budi; Sinukaban, Naik; Murtilaksono, Kukuh; Sanim, Bunasor (UNIVERSITY OF LAMPUNG, 2011)
Way Betung watershed is one of the important water resources in Lampung Province and it provides a clean water for Bandar Lampung City through a regional water supply company (PDAM). By the increase of population and economical activities of Bandar Lampung City, the need of clean water also increase, however by the time, the conditions of Way Betung watershed as water resources are declining. Therefore, to improve or to restore WayBetung watershed, a high cost is needed. The research was aimed: (a) to study the effects of Way Betung watershed land use change on the water resources of Bandar Lampung City, (b) to arrange the sustainable development of Way Betung watershed in order to maintain the availability of water resources. The sustainable developments of water resources of Way Betung watershed were arranged in five alternatives/scenarios and each alternative was related toits erosion (USLE method) and its run off volume (SCS method). The results showed that land use changes of Way Betung watershed (1991-2006) were likely to increase daily maximum discharge (Q max), to decrease daily minimum discharge (Q min), to increase fluctuation of river discharge, and to increase yearly run off coeffcient. The best sustainable development of water resources of Way Betung watershed, Lampung Province, was alternative/scenario-4 (forest as 30% of watershed areas + alley cropping in the mix garden). This alternative will decrease erosion to the level lower than tolerable soil loss and also decrease fluctuation of monthly run off.Keywords: Land use change, run off coefficient, water resources, watershed